MARKETING ASPECTS OF THE APPLICATION OF "FORMULA 4 K" IN THE IMPLEMENTATION OF GRANT PROGRAMS - KOVALCHUK, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The higher school of Ukraine has undergone significant transformational changes in recent years, initially due to the processes caused by the "Covid-19" pandemic in 2019-2021, and since February 24, 2022, the military aggression of the Russian Federation against Ukraine has been added to the destructive factors of influence. Factors that had a significant impact on the development of higher education in recent years include: 1) a decrease in the quality of secondary education as a result of existing restrictions, which requires additional efforts on the part of professors and teachers of higher education institutions (HEIs) in the formation of professional competences according to the educational programs chosen by the applicants; 2) the formation of the effect of "reduced concentration of attention" among students - representatives of the "Z" and "ALPHA" generations, who grew up on digital technologies and perceive them as an integral part of their real life, began to enter universities; 3) limitation of work in classrooms, and therefore: reduction of direct contacts of students with teachers, which does not allow the full use of existing innovative learning technologies, and also requires greater independence and responsibility from students and the formation of specific skills among the teaching staff; 4) the influence of stress factors on the psycho-emotional state of both applicants and teachers, hence the urgent need to conduct special classes with professional psychologists to overcome them (unfortunately, not every institution of higher education has such specialists); 5) physical destruction of educational, economic and infrastructure institutions of Ukraine, which led to their relocation to safer regions of the country, and therefore increased competition in the central and western regions, etc. But crisis phenomena are usually the best stimulus for development and innovation, prompting the search for non-standard responses to overcome them. One of the directions for overcoming crisis phenomena and their consequences for the system of pre-higher and higher education and the economy as a whole can be the application of the "4K Formula", because it is this approach to education that is focused on the formation of skills in the individual, which are needed not only now, but also will be in demand in the future.The article discusses the marketing aspects of the application of the "4 K formula" in the implementation of the grant project "Expanding the horizons of opportunities for Khmelnytskyi residents and IDPs "Khmelnytskyi: Cooperation & Training & Integration". Theoretical approaches to the formation of the "4K" concept were considered and analyzed.